Discovery and exploration of widespread infection of mycoviruses in Phomopsis vexans, the causal agent of phomopsis blight of eggplant in China - Xie, Fang Ling; Zhou, Xin Yu; Xiao, Rong; Zhang, Chao Jun; Zhong, Jie; Zhou, Qian; Liu, Feng; Zhu, Hong Jian (Frontiers in Plant Science, 2022)
Phomopsis vexans, which causes Phomopsis blight of eggplant, has been reported worldwide. To study the biocontrol of this disease, 162 leaf and fruit samples of eggplant Phomopsis blight were collected from Hunan, Hubei, Jiangxi, Sichuan, Zhejiang, Fujian, Guangdong and Anhui Provinces from 2017 to 2019. Eighty-seven pathogenic fungus isolates were identified as P. vexans. The following studies were conducted: screening of sporulation medium, spore morphology analysis, mycovirus detection and identification of novel mycoviruses in these isolates. The results showed that eggplant tissue medium was the most suitable medium for rapid sporulation, and all isolates had mycoviruses consisting of mainly mixed infections. The genome of these mycoviruses varied from 1-15 kb. Five novel mycoviruses infecting P. vexans were obtained, including “Phomopsis vexans fusarivirus 1” (PvFV1), “Phomopsis vexans ourmia-like virus 1” (PvOLV1), “Phomopsis vexans endornavirus 2” (PvEV2), “Phomopsis vexans partitivirus 1” (PvPV1) and “Phomopsis vexans victorivirus L1” (PvVVL1). Thus, PvVVL1 displays a unique genome structure, and this is the first report of a victorivirus consisting of two segments and of a deltapartitivirus infecting the fungus host.